Technical entrepreneurship, strategic awareness and corporate transformation in small high-tech firms - Berry, M.M.J (Technovation)
This paper presents the results of an empirical study of the management phenomenon underlying corporate transformation processes in small high-tech firms. Within a few years of their foundation, small high-tech firms must evolve from a technology-driven to a market-led management philosophy. In order to support this transition towards a marketing orientation there must be a concurrent development in management practice within the organization if the firm is to survive and be successful in the long term. It is argued that firms are unlikely to achieve corporate transformation unless a strategic approach to managing the business and technology development is adopted. Significantly, firms that fail to evolve towards a market-led organization and a strategic orientation are those where management is dominated by technologists. It is concluded that the strategic awareness of the technical entrepreneur is a critical determinant of the firm's viability and achievements in the long term. It is further proposed that policy instruments should focus upon developing not only the technological base but also the general management and marketing skills base of small high-tech firms in order to ensure their continued effective contribution to innovation and international competitiveness.